In-service teachers' self-efficacy to practice inclusive education at public primary schools in the Amhara region: Implications for teacher education - Tsegie Genet Zegeye; Solomon Kassie Alem; Ayetenew Abie (Bahir Dar Journal of Education)
The purpose of this study was to investigate teachers' self-efficacy for practicing inclusive education at public primary schools in the Amhara region and examining the effect of teachers’ gender, level of education, and teaching experience. The study used a survey design. Participants included 336 public primary school teachers selected using a stratified systematic random sampling technique. The teacher Efficacy for Inclusive Practice (TEIP) scale was administered to sample teachers. Data were analyzed using descriptive and inferential statistical techniques. Teachers showed low level of self-efficacy on the TEIP scale. While gender did generate variations in teacher self-efficacy for practicing inclusive education, level of education and teaching experience did not generate significant variations. The results generally revealed that teachers had low sense of self-efficacy to practice inclusive education. It implies that the knowledge and skills teachers gained in special needs and inclusive education in teacher training programs were not adequate enough to practice inclusive education. Therefore, to make inclusive education useful for all students including students with special needs, it is essential to revisit teacher training programs in Ethiopia.